CONCEPTUAL ASPECTS OF THE MANAGEMENT OF INNOVATIVE DEVELOPMENT OF REGIONS AT THE NATIONAL LEVEL - BABAYEV, VOLODYMYR; SUKHONOS, MARIA; DYMCHENKO, OLENA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The reforms of the restructuring of the national and regional development management system combine such components as: transition of national and regional policy to a new system level consolidation of territorial units; decentralization of power; formation of a new model of local self-government; changes in the administrative-territorial structure. The complex of the listed components of the studied reform process proceeds in time together and in interactions between subjects of the power, creating at the same time extremely difficult situation for understanding and carrying out actions. This system is also complex and multidisciplinary. It should use: legal norms; institutional norms; economic characteristics and indicators; organizational and managerial models, mechanisms and technologies and much more. Thus, there is a need for a reasoned solution to the development and adoption of a new theoretical and methodological approach to solving this problem.
Keywords: innovative development; national development; regional development; region